A Novel Instructional Approach to the Design of Standard Controllers: Using Inversion Formulae - Ntogramatzidis, Lorenzo; Zanasi, R.; Cuoghi, S. (IEEE, 2014)
This paper describes a range of design techniques for standard compensators (Lead-Lag networks and PID controllers) that have been applied to the teaching of many undergraduate control courses throughout Italy over the last twenty years, but that have received little attention elsewhere. These techniques hinge upon a set of simple formulas—herein referred to as Inversion Formulae—for the computation of the parameters of the controller as functions of the typical specifications of steady-state performance, stability margins, and crossover frequency.